1996
DOI: 10.1139/m96-051
|View full text |Cite
|
Sign up to set email alerts
|

An overview of microbial research related to high-level nuclear waste disposal with emphasis on the Canadian concept for the disposal of nuclear fuel waste

Abstract: Current research on the effects of microbiology on nuclear waste disposal, carried out in a number of countries, is summarized. Atomic Energy of Canada Limited has developed a concept for the permanent disposal of nuclear fuel waste in Canada. A program was initiated in 1991 to address and quantify the potential effects of microbial action on the integrity of the multibarrier system on which the disposal concept is based. This microbial program focuses on answering specific questions in areas such as the survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…Potential microbiological contamination of sampled core is well recognised (e.g. Stroes-Gascoyne and West, 1996;Chapelle, 2000;Stroes-Gascoyne et al, 2007;Hallbeck and Pedersen, 2008;Polson et al, 2010) and the current study further illustrates this fact. However, the markedly different biological structures observed in the post-experimental biotic material were interpreted as a filamentous biofilm resulting from the activity of P. denitrificans introduced during the experiment.…”
Section: Abiotic Column Experiments -Post-experimental Materialssupporting
confidence: 70%
“…Potential microbiological contamination of sampled core is well recognised (e.g. Stroes-Gascoyne and West, 1996;Chapelle, 2000;Stroes-Gascoyne et al, 2007;Hallbeck and Pedersen, 2008;Polson et al, 2010) and the current study further illustrates this fact. However, the markedly different biological structures observed in the post-experimental biotic material were interpreted as a filamentous biofilm resulting from the activity of P. denitrificans introduced during the experiment.…”
Section: Abiotic Column Experiments -Post-experimental Materialssupporting
confidence: 70%
“…As shown in Figure 3a, no significant relationship was seen between ignition loss (an index of organic matter content) and bacterial numbers in the bentonite samples. The weak correlation is expected if we assume that most organics in bentonite do not promote bacterial growth; the organic carbon naturally present in the buffer and backfill clays may be difficult to degrade (Stroes-Gascoyne and West 1996). On the contrary, it was demonstrated that bacterial numbers tended to decrease FIG.…”
Section: Discussionmentioning
confidence: 96%
“…Irradiation experiments and a buffer container experiment in the underground research laboratory of Atomic Energy of Canada Limited (AECL) indicated detrimental effects of heat and radiation on the naturally present microflora in buffer materials. The results suggested that radiation and desiccation create a zone of depleted or reduced microbial activity extending for a few tens of cm into buffer material (Stroes-Gascoyne and West 1996).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Regardless of their location and detailed design, DGR are generally inhospitable environments for microbial activity. 2,[8][9][10][11][12] The various microbial stressors in the repository are elevated temperature, absence or lack of free water, absence or lack of nutrients and/ or terminal electron acceptors, saline pore waters and groundwaters, redox conditions, mechanical forces from the swelling of smectitic clays, and radiation fields. While specific microbes can be identified that are tolerant to each of these stressors, the combined effect of a number of stressors is to limit the diversity of the biota.…”
Section: Introductionmentioning
confidence: 99%